Epistemology and practice: Durkheim's The elementary forms of religious life - Rawls, Anne Warfield (Cambridge University Press, 2004)
In this original and controversial book Professor Rawls argues that Durkheim's The Elementary Forms of Religious Life is the crowning achievement of his sociological endeavour and that since its publication in English in 1915 it has been consistently misunderstood. Rather than a work on primitive religion or the sociology of knowledge, Rawls asserts that it is an attempt by Durkheim to establish a unique epistemological basis for the study of sociology and moral relations. By privileging social practice over beliefs and ideas, it avoids the dilemmas inherent in philosophical approaches to knowledge and morality that are based on individualism and the tendency to privilege beliefs and ideas over practices, both tendencies that dominate western thought. Based on detailed textual analysis of the primary text, this book will be an important and original contribution to contemporary debates on social theory and philosophy.